The FoMO and Impulsive Buying: The Mediating Role of Social Media Comparison and Moderating Effect of Social Media Envy: A study among Indonesian Gen Z Social Media Users - Hizbullah, Saif Syahsyah; Rabbani, Inayah Abdillah; Swastika, Yuan; Maksar, Muhammad Sofian (Jurnal Ilmiah Akuntansi Manajemen, 2026)
This study aims to investigate the influence of Fear of Missing Out (FoMO) on Impulsive Buying (IB), with Social Media Comparison (SMC) examined as a mediating variable and Social Media Envy (SME) as a potential moderator. The research addresses the increasing psychological impact of social media usage on consumer behavior, particularly among digital-native users—especially Gen Z aged 17 to 28 years who visit coffee shops as a lifestyle activity at least once per month. A quantitative survey approach was employed, and data were collected from 112 respondents using an online questionnaire. All constructs were tested for validity and reliability, with Cronbach’s alpha values ranging from 0.68 to 0.79. Confirmatory Factor Analysis (CFA) indicated good model fit (CFI = 0.926, TLI = 0.907, RMSEA = 0.065). Structural Equation Modeling (SEM) was used to test the hypothesized relationships. The results show that FoMO has a significant direct effect on impulsive buying behavior (β = 0.641, p = 0.007), confirming its central role. However, the mediating effect of SMC was not supported, as the indirect path was not statistically significant (p = 0.258). Similarly, moderation analysis using interaction regression revealed that SME did not significantly moderate the effect of SMC on IB (p = 0.109), although SME had a significant direct effect on IB (p < 0.001). Multi-group analysis based on gender showed that the influence of FoMO on IB was stronger and statistically significant among female participants compared to males. These findings suggest that FoMO is a consistent predictor of impulsive buying in social media contexts, although the expected mediating and moderating mechanisms through comparison and envy may not be as influential as theorized.